1999
DOI: 10.1088/0268-1242/14/10/308
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of thin films and quantum wells of InxGa1-xN/GaN and their dependence on laser irradiation

Abstract: We have grown bulk In x Ga 1−x N films and In x Ga 1−x N/GaN (x 0.1) multiple quantum well structures on Al 2 O 3 substrates by electron cyclotron resonance assisted molecular beam epitaxy. We have not found any signs of phase separation in bulk films with low indium content, x 0.1. However, we observed inhomogeneous spatial distribution of indium with x varying from 0.1 to 0.2. In multiple quantum well structures with thin In x Ga 1−x N layers non-homogeneity was absent under certain growth conditions. Exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…With this differential field around the specimen apex, it is not possible to measure a uniform composition across the specimen, a conclusion also reached by Mancini et al 31 Additional support for an athermal process can be found in estimating the temperature increase due to the laser pulse using an adiabatic approximation, ΔT = Iτβ/C p , where ΔT is the temperature change, I is the laser intensity, τ is the laser pulse length, β is the absorption coefficient, and C p is the heat capacity. 62 Taking τ = 10 ps, β = 1.5 × 10 5 cm −1 , 63 C p = 1 J/ cm 3 •K, 64 and I = 1 × 10 6 W/cm 2 for 0.02 pJ (which gave the expected GaN stoichiometry as shown in Figure 8a) gives a ΔT ≈ 2 K. Even with the absorption coefficient enhanced to be fully metal-like due to the high fields, 6 this laser-induced temperature change would be only 20 K, which was shown by the measurements where the base temperature was changed to be insufficient to affect a significant change in the evaporation behavior. At relatively high laser energies (>1 pJ), previous research has shown evaporation displaying an apparent lack of nitrogen on the side of the specimen where the laser is incident.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this differential field around the specimen apex, it is not possible to measure a uniform composition across the specimen, a conclusion also reached by Mancini et al 31 Additional support for an athermal process can be found in estimating the temperature increase due to the laser pulse using an adiabatic approximation, ΔT = Iτβ/C p , where ΔT is the temperature change, I is the laser intensity, τ is the laser pulse length, β is the absorption coefficient, and C p is the heat capacity. 62 Taking τ = 10 ps, β = 1.5 × 10 5 cm −1 , 63 C p = 1 J/ cm 3 •K, 64 and I = 1 × 10 6 W/cm 2 for 0.02 pJ (which gave the expected GaN stoichiometry as shown in Figure 8a) gives a ΔT ≈ 2 K. Even with the absorption coefficient enhanced to be fully metal-like due to the high fields, 6 this laser-induced temperature change would be only 20 K, which was shown by the measurements where the base temperature was changed to be insufficient to affect a significant change in the evaporation behavior. At relatively high laser energies (>1 pJ), previous research has shown evaporation displaying an apparent lack of nitrogen on the side of the specimen where the laser is incident.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 22 specimen apex, it is not possible to measure a uniform composition across the specimen; a conclusion also reached by Mancini et al 31 Additional support for an athermal process can be found in estimating the temperature increase due to the laser pulse using an adiabatic approximation, ∆T = Iτβ/C p , where ∆T is the temperature change, I is the laser intensity, τ is the laser pulse length, β is the absorption coefficient, and C p is the heat capacity. 62 T...…”
Section: Ganmentioning
confidence: 99%